Computer assisted assessment : research into e-assessment : 18th International Conference, CAA 2015, Zeist, the Netherlands, June 22-23, 2015. Proceedings /: research into e-assessment : 18th International Conference, CAA 2015, Zeist, the Netherlands, June 22-23, 2015. Proceedings. (2015) - Unknown
No abstract available